Psychosocial predictors and psychological prevention of soccer injuries: A systematic review and meta-analysis of the literature. (July 2018) - Slimani, Maamer; Bragazzi, Nicola Luigi; Znazen, Hela; Paravlic, Armin; Azaiez, Fairouz; Tod, David
Abstract: Objectives: To examine (a) the relationships between the psychosocial risk factors and injury rates and (b) the effects of psychological-based prevention interventions on the injury risk of soccer players. Design: Scholarly electronic databases (PubMed/MEDLINE, Google Scholar, Scopus) were searched on 1 January 2017, complemented by manual searches of bibliographies. Setting: Systematic review and meta-analysis. Participants: We identified 13 eligible studies, including a total of 1149 injured soccer players aged between 14 and 36 years. Main outcome measures: Psychosocial risk factors, psychological-based prevention interventions and injury risk in soccer players. Results: Personality traits, such as trait anxiety and perceived mastery climate, along with a history of stressors, like negative-life-event stress or high level of life stress, daily hassle, and previous injury, are the main predictors of injury rates among soccer players. Also, from injury prevention studies, it has been shown that psychological-based interventions reduce injury rates (effect size = 0.96; 95% CI 0.34–1.58; p = 0.002) in senior soccer players. Conclusions: Practitioners need to ensure injured soccer players are psychologically and socially ready to play. They should also employ psychological-based interventions (i.e., mindfulness, imagery, self-talk, stress management, relaxation, goal setting) when designing injury prevention programs. Highlights: History of stressors and personality attributes are the main predictors of injury rates among soccer players. Psychological-based prevention interventions might have potential to reduce the frequency of soccer injuries. This review suggests that the player who can effectively manage life stress and anxiety will be less likely to be injured. Since the effectiveness of psychological interventions was evident only in 1/3 of studies, further research is needed.